2020
DOI: 10.1002/wat2.1412
|View full text |Cite
|
Sign up to set email alerts
|

Global atmospheric moisture transport associated with precipitation extremes: Mechanisms and climate change impacts

Abstract: The atmospheric moisture transport processes are of great importance to the occurrence and intensity of precipitation extremes. In this paper, we review the linkage between processes, including the large‐scale atmospheric circulation, atmospheric moisture transport, and extreme precipitation events. We first summarize the thermodynamic and dynamic processes and moisture transport trackings for historical precipitation extremes. We then focus on the contribution of three major atmospheric moisture transport pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 241 publications
(380 reference statements)
0
37
0
Order By: Relevance
“…Although the focus on intense moisture transport and the use of IVT is very prominent in studies of extreme precipitation, investigations of the large-scale circulation processes that drive the moisture transport often remain more in the background and less understood. Few studies combined the use of PV and IVT and linked Rossby wave breaking to moist air incursions into the Arctic (Liu and Barnes, 2015), and to the formation and landfall of atmospheric rivers Magnusdottir, 2014, 2016;Hu et al, 2017;Zavadoff and Kirtman, 2020). Several extreme precipitation-related studies took Rossby wave breaking as a starting point and linked this process to enhanced moisture transport (Martius et al, 2006;Ryoo et al, 2013;Moore et al, 2019), whereas others took the perspective of moisture transport and identified some form of upper-level forcing in the shape of upper-level troughs and/or cutoffs upstream, suggesting the occurrence of Rossby wave breaking (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although the focus on intense moisture transport and the use of IVT is very prominent in studies of extreme precipitation, investigations of the large-scale circulation processes that drive the moisture transport often remain more in the background and less understood. Few studies combined the use of PV and IVT and linked Rossby wave breaking to moist air incursions into the Arctic (Liu and Barnes, 2015), and to the formation and landfall of atmospheric rivers Magnusdottir, 2014, 2016;Hu et al, 2017;Zavadoff and Kirtman, 2020). Several extreme precipitation-related studies took Rossby wave breaking as a starting point and linked this process to enhanced moisture transport (Martius et al, 2006;Ryoo et al, 2013;Moore et al, 2019), whereas others took the perspective of moisture transport and identified some form of upper-level forcing in the shape of upper-level troughs and/or cutoffs upstream, suggesting the occurrence of Rossby wave breaking (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…al., 2015;Espinoza et al, 2018;Benedict et al, 2019;Hsu and Chen, 2020;Sousa et al, 2020). For extensive reviews on the link between intense moisture transport and EPEs, the reader is referred to Gimeno et al (2016) and Liu et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…There is a large body of literature which examines the relationship between large‐scale atmospheric circulations and regional precipitation patterns (e.g., Liu et al, 2020, and references therein). Wang and Chen (2009) showed that the Great Plains low‐level jet (GPLLJ) can be attributed to late‐spring extreme rainfall events over the central United States.…”
Section: Introductionmentioning
confidence: 99%